Conundra and Progress: Research on Entry Order and Performance - Lieberman, M.B (Institutional Knowledge at Singapore Management University, 2013)
We raise four sets of issues relating to the definition and measurement of first mover advantage. We begin by posing questions about the basic definition of FMA and whether advantage should be measured in terms of profit, market share or business survival — which often yield conflicting results. We then probe the related question of duration — over what period of time must superior performance be sustained to constitute first mover advantage? Next we consider problems of identifying the starting date of a market and the basic question of how markets should be defined. Last, we consider a potentially important type of sample selection bias that has largely been overlooked. We conclude by assessing recent progress in entry order research.